Using smart phones in electronic agricultural extension directed to farmers - يارا طلال احسان ,; محمود عليو,; بسيم برهوم,; حيان سليمان, (Latakia University Journal -Biological Sciences Series, 2024)
This research aims to study the personal and social characteristics of farmers who use smart phones in the study area and to study the possibility of using them in agricultural extension by farmers through applications designed for that. A questionnaire was used and distributed to the respondents. The sample included 100 farmers in the four regions of Latakia Governorate, namely Latakia Center, Jableh, Al-Haffa, and Qardaha. The descriptive approach was used to analyze data such as frequencies, percentages, arithmetic averages, five-point Likert scale, and others among the sample members. The results showed that all members of the sample own mobile phones, 79% of them are modern devices, and 83% have Internet service, and they have the ability to use them to a moderate degree. Smartphones were an important source of information for farmers to a moderate degree, and therefore there is a noticeable interest from farmers in obtaining On modern agricultural information via smart phones and the Internet, farmers positively accept the use of smart phones in agricultural extension, which confirms that there is a possibility of developing electronic extension applications on smart phones due to the availability of appropriate conditions, as it will be popular and accepted by farmers. The research concluded with a set of recommendations, the first of which was the provision of electronic extension applications, the necessity of disseminating and promoting the culture of their use and motivating farmers to adopt them, in addition to conducting training courses in the field of information and communications technology in extension units in order to move towards electronic agricultural extension.